Pengaruh Kepatuhan K3, Stres Kerja, dan Kompensasi Terhadap Produktivitas Karyawan Pada PT. Saraswanti Anugerah Makmur Tbk Unit Pabrik Medan - Donald Frensius Pasaribu; Fauzan Azim; Anita Novialumi; Yenny Lisbeth Siahaan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
This research examines how adherence to Occupational Health and Safety (OHS) standards, work-related stress, and enhancements impact worker productivity at the Medan Fertilizer Factory. These aspects are considered vital in influencing labor productivity. A quantitative approach was adopted, employing a survey method that involved 180 employees who participated as respondents. Data analysis was performed using SPSS version 27, applying multiple linear regression to explore the associations between independent variables (OHS, work stress, compensation) and dependent variables (worker productivity). Findings indicate that adherence to OHS regulations significantly boosts productivity, whereas work-related stress detracts from employee output. Additionally, fair and adequate compensation positively influences productivity levels. There is also a combined effect where compliance with OHS, work stress, and compensation collectively enhance employee productivity. These results highlight the necessity for robust OHS practices, effective stress management strategies, and suitable compensation frameworks to enhance worker productivity at the Medan Fertilizer Factory and other similar businesses. Keywords: Occupational health and safety (OHS), work stress, compensation, and work productivity